3 The comorbidity between epilepsy and dissociative seizures. (28th May 2019) - Reuber, Markus
Abstract : Professor Reuber joined the Univ of Sheffield in 2005. He also works at the Royal Hallamshire Hospital and the Chesterfield Royal Hospital as an Honorary Consultant Neurologist. His clinical work focuses on the treatment of patients with epilepsy and other seizure disorders. He leads the Epilepsy Research Group in the Academic Neurology Unit and is the Epilepsy Research Theme Lead in the Clinical Neuroscience Directorate at Sheffield Teaching Hospitals. He is chair of the Neurosciences Local Priority Group of the Comprehensive Local Research Network and represents South Yorkshire on the National Speciality Group for Nervous System Disorders. He completed his undergraduate medical education in Cologne, Germany, and Nottingham. He pursued neurological training in Leeds, and at the Department of Epileptology of the University of Bonn, Germany. Dissociative seizures are experiential and behavioural responses to internal or external triggers. They superficially resemble epileptic seizures in terms of their subjective and objective manifestations. Although they are theoretically distinct from epileptic seizures in which seizure manifestations are related to hypersynchronous and excessive discharges in the brain, there is a complex relationship between epileptic and dissociative seizures, which extends beyond the (clinically extremely important) problem of misdiagnosis. While epilepsy is more closely associated with clinically detectable structural or biochemical abnormalities than dissociative seizures, the sort of experiential factors which are widely recognized as predisposing individuals to the development of dissociative seizures (such as trauma and neglect in early life) also increase the risk of developing epilepsy. The similar (albeit not identical) developmental background of patients with epilepsy on the one hand and dissociative seizures on the other is reflected by similar (but not identical) psychiatric comorbidity profiles. More specifically, epileptic seizures are a risk factor for the development of dissociative seizures, may precipitate or trigger dissociative seizures, and comorbid epilepsy may contribute to the perpetuation of dissociative seizures disorders. My talk will provide some food for thought about two seizure disorders often associated with high levels of disability which are theoretically different but which - in practice - have much in common. References: Kutlubaev MA, et al. Dual diagnosis of epilepsy and psychogenic nonepileptic seizures: Systematic review and meta-analysis of frequency, correlates, and outcomes. Epilepsy and Behav 2018;89:70–78. Brown RJ, Reuber M. Psychological and psychiatric aspects of psychogenic non-epileptic seizures (PNES): A systematic review. Clin Psychol Rev 2016;45:157–182. Brown RJ, Reuber M. Towards an integrative theory of psychogenic non-epileptic seizures (PNES). Clin Psychol Rev 2016;47:55–70. Reuber M & Brown RJ. Understanding psychogenic nonepileptic seizures-Phenomenology, semiology and the Integrative Cognitive Model. Seizure 2017;44:199–205. Brown RJ, Baroni G et al. Variables associated with co-existing epileptic and psychogenic nonepileptic seizures: a systematic review. Seizure 2016;37:35–40.